Linking S. aureus Immune Evasion Mechanisms to Staphylococcal Vaccine Failures - Irshad Ahmed Hajam; George Y. Liu (MDPI AG, 2024)
Vaccination arguably remains the only long-term strategy to limit the spread of S. aureus infections and its related antibiotic resistance. To date, however, all staphylococcal vaccines tested in clinical trials have failed. In this review, we propose that the failure of S. aureus vaccines is intricately linked to prior host exposure to S. aureus and the pathogen's capacity to evade adaptive immune defenses. We suggest that non-protective immune imprints created by previous exposure to S. aureus are preferentially recalled by SA vaccines, and IL-10 induced by S. aureus plays a unique role in shaping these non-protective anti-staphylococcal immune responses. We discuss how S. aureus modifies the host immune landscape, which thereby necessitates alternative approaches to develop successful staphylococcal vaccines.